Implication of REDD1 in the activation of inflammatory pathways - Faustine Pastor (Nature Portfolio, 2017)
Abstract In response to endotoxemia, the organism triggers an inflammatory response, and the visceral adipose tissue represents a major source of proinflammatory cytokines. The regulation of inflammation response in the adipose tissue is thus of crucial importance. We demonstrated that Regulated in development and DNA damage response-1 (REDD1) is involved in inflammation. REDD1 expression was increased in response to lipopolysaccharide (LPS) in bone marrow derived macrophages (BMDM) and in epidydimal adipose tissue. Loss of REDD1 protected the development of inflammation, since the expression of proinflammatory cytokines (TNFα, IL-6, IL-1β) was decreased in adipose tissue of REDD1−/− mice injected with LPS compared to wild-type mice. This decrease was associated with an inhibition of the activation of p38MAPK, JNK, NF-κB and NLRP3 inflammasome leading to a reduction of IL-1β secretion in response to LPS and ATP in REDD1−/− BMDM. Although REDD1 is an inhibitor of mTORC1, loss of REDD1 decreased inflammation independently of mTORC1 activation but more likely through oxidative stress regulation. Absence of REDD1 decreases ROS associated with a dysregulation of Nox-1 and GPx3 expression. Absence of REDD1 in macrophages decreases the development of insulin resistance in adipocyte-macrophage coculture. Altogether, REDD1 appears to be a key player in the control of inflammation.